2008
DOI: 10.4137/ccrpm.s773
|View full text |Cite
|
Sign up to set email alerts
|

The Unpredictable Effect of Changing Cardiac Output on Hypoxemia after Acute Pulmonary Thromboembolism

Abstract: Previous studies reported that the degree of hypoxemia following acute pulmonary thromboembolism (APTE) was highly variable and that its mechanism was mainly due to the creation of many high and low ventilation/perfusion (V/Q) units, as a result of the heterogeneous regional blood fl ow (Q) caused by embolic obstruction. We studied the effect of changing cardiac output (Q t ) on gas exchange after APTE in 5 embolized piglets (23 ± 3 Kg), using Dobutamine intermittently at approximately 20 µg/kg/min for 120 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Others showed similar results using fluid and other vasopressors 18 . A recent study also confirmed that when Qt was increased intermittently by dobutamine after APTE, PaO 2 did not improve and sometimes worsened 36 . Upon further analysis, this variation of hypoxemia at higher Qt was mostly accounted for by the interplay between the beneficial effect of higher PvO 2 on PaO 2 and the deleterious effect of worsening V‐Q mismatch, caused by the maldistribution of regional Q, as demonstrated by the FMS data 36 …”
Section: Mechanisms Of Hypoxemia Following Aptementioning
confidence: 65%
See 2 more Smart Citations
“…Others showed similar results using fluid and other vasopressors 18 . A recent study also confirmed that when Qt was increased intermittently by dobutamine after APTE, PaO 2 did not improve and sometimes worsened 36 . Upon further analysis, this variation of hypoxemia at higher Qt was mostly accounted for by the interplay between the beneficial effect of higher PvO 2 on PaO 2 and the deleterious effect of worsening V‐Q mismatch, caused by the maldistribution of regional Q, as demonstrated by the FMS data 36 …”
Section: Mechanisms Of Hypoxemia Following Aptementioning
confidence: 65%
“…18 A recent study also confirmed that when Qt was increased intermittently by dobutamine after APTE, PaO 2 did not improve and sometimes worsened. 36 Upon further analysis, this variation of hypoxemia at higher Qt was mostly accounted for by the interplay between the beneficial effect of higher PvO 2 on PaO 2 and the deleterious effect of worsening V-Q mismatch, caused by the maldistribution of regional Q, as demonstrated by the FMS data. 36 Earlier reports have shown that during severe shock following acute pulmonary embolism, the degree of hypoxemia did not reflect the severity of embolic obstruction.…”
Section: Gas Exchange In Aptementioning
confidence: 99%
See 1 more Smart Citation